Nano separation membrane material for separating oil-containing wastewater as well as preparation method and application of nano separation membrane material

By anchoring a polydopamine@ZnIn2S4-CuS heterostructure on a nano-based membrane, a gear-shaped PN-type heterojunction was constructed, which solved the problems of limited oil-water separation flux and poor anti-fouling performance of existing separation membrane materials, and achieved synergistic treatment of efficient oil-water separation and degradation of organic pollutants.

CN121041879AActive Publication Date: 2025-12-02SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202511612061.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2025-12-02
Estimated Expiration
2045-11-06

AI Technical Summary

Technical Problem

Existing separation membrane materials have limited oil-water separation flux and poor anti-fouling performance when treating oil-water wastewater containing a large number of tiny oil droplets and pollutants, making it difficult to achieve efficient separation and degradation.

Method used

Anchoring polydopamine@ZnIn2S4-CuS heterostructures on nanofilms to construct gear-shaped PN heterojunctions achieves synergistic enhancement of photothermal conversion and photocatalytic functions, forming a three-dimensional network structure to improve separation flux and anti-fouling performance.

Benefits of technology

It achieves synergistic enhancement of high separation flux and anti-pollutant treatment. The nano-separation membrane material can rapidly separate oil and water and simultaneously degrade organic pollutants under visible light. The separation flux reaches 3921.44±196.1 L·m-2·h-1, the rejection rate exceeds 99.5%, and the photocatalytic degradation efficiency is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121041879A_ABST
    Figure CN121041879A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of separation of oil-containing wastewater, and particularly discloses a nano separation membrane material for separating oil-containing wastewater as well as a preparation method and application of the nano separation membrane material aiming at the problems of limited oil-water separation flux, poor anti-pollution performance and the like of a separation membrane material for treating the oil-containing wastewater at present. The nano separation membrane material comprises a nano base membrane and polydopamine (at) ZnIn2S4-CuS anchored on the surface of the nano base membrane, and the polydopamine (at) ZnIn2S4-CuS is a gear-shaped ZnIn2S4-CuS heterojunction material bridged with dopamine. According to the nano separation membrane material, through the gear-shaped ZnIn2S4-CuS heterojunction, the ultrahigh oil-water separation flux is achieved, the photocatalysis-photothermal conversion performance is achieved through the synergistic effect of ZnIn2S4-CuS and the polydopamine layer, and a feasible separation membrane material is provided for efficient separation treatment of complex emulsified oily wastewater; and meanwhile, the synergistic effect of gear-shaped CuS and ZnIn2S4 is utilized to promote efficient transfer of photo-induced electrons, generate abundant active substances, quickly degrade organic pollutants in the oily wastewater and play an anti-pollution role.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oily wastewater separation technology, and more specifically, to a nano-separation membrane material for oily wastewater separation, its preparation method, and its application. Background Technology

[0002] In oil-rich industries such as petroleum exploration and development, shipping, and fine chemicals, the efficient treatment of complex emulsified oily wastewater has always been a serious challenge for water purification technology. This type of wastewater has a complex composition, containing not only a large number of difficult-to-separate micro-oil droplets but also various stubborn organic pollutants, making deep purification difficult with conventional treatment methods. Therefore, membrane separation technology has been proposed, offering significant advantages in separation precision. However, single-function membrane materials typically have the following technical shortcomings: on the one hand, they struggle to simultaneously achieve efficient separation and pollutant degradation, limiting treatment efficiency; on the other hand, they are unable to handle complex membrane fouling problems, resulting in a significant reduction in membrane material lifespan.

[0003] In recent years, photothermal conversion technology has attracted much attention for its ability to enhance mass transfer and separation. For example, patent CN117815707A proposes a method for preparing a photothermal-driven pH-responsive oil-water separation composite membrane. By combining a flexible and inexpensive polypropylene membrane with a pH-responsive polymer containing tertiary amine groups prepared through free radical polymerization, an environmentally friendly and more cost-effective pH-responsive oil-water separation membrane is prepared. This membrane can achieve high-level purification of complex wastewater and intelligent switching between oil and water separation, and also has heavy metal adsorption properties.

[0004] Photocatalysis technology has shown great potential in the field of pollutant degradation. For example, patent CN110860218A provides a method for preparing a PAN-based oil-water separation microporous membrane with photocatalytic function. The method involves introducing SiO2 nanoparticles onto the outer surface of TiO2 using a sol-gel method to coat the photocatalytic nano-TiO2, resulting in a SiO2@TiO2 additive. Then, SiO2@TiO2 is blended with P(AN-MA) to prepare a casting solution. The casting solution containing the SiO2@TiO2 additive is then solidified into a membrane using the TIPS method. The solidified membrane is then hydrolyzed to convert the cyano groups on the membrane surface into hydrophilic carboxyl groups, while simultaneously dissolving the SiO2 shell of the additive. The TiO2 inside the additive is released and migrates to the membrane surface, achieving efficient utilization of the photocatalytic particles without damaging the original properties of the base membrane. This yields a PAN-based microporous membrane with both oil-water separation and photocatalytic degradation capabilities.

[0005] However, traditional photocatalytic materials suffer from low carrier separation efficiency and narrow light absorption range, resulting in insufficient catalytic activity. While single photothermal materials can achieve localized heating, they cannot simultaneously and completely degrade pollutants, making it difficult to achieve efficient separation and degradation. Furthermore, the idea of ​​synergistic treatment by photothermal and photocatalytic technologies is often limited by their own structure and performance, resulting in independent processes or even energy competition, making it difficult to achieve a synergistic enhancement effect and thus currently difficult to realize.

[0006] In summary, current methods for treating oily-water wastewater containing a large number of tiny oil droplets and pollutants suffer from problems such as limited oil-water separation flux and poor anti-fouling performance of separation membrane materials. Summary of the Invention

[0007] The purpose of this invention is to solve the problems of limited oil-water separation flux and poor anti-fouling performance of current separation membrane materials used for oil-water wastewater treatment. By anchoring a bioadhesive dopamine-bridged gear-shaped ZnIn2S4-CuS heterostructure onto a nano-based membrane, a polymer composite membrane with high separation flux as its core advantage and efficient photocatalytic-photothermal conversion function has been successfully prepared, breaking through the technical bottlenecks that traditional separation membrane materials cannot overcome in terms of oil-water separation flux and anti-fouling performance.

[0008] This invention is achieved through the following technical solution: This invention provides a nano-separation membrane material for separating oily wastewater, comprising a nano-base membrane and polydopamine@ZnIn2S4-CuS anchored on the surface of the nano-base membrane. The polydopamine@ZnIn2S4-CuS is a gear-shaped ZnIn2S4-CuS heterojunction material bridging dopamine.

[0009] The key technical feature of the nano-separation membrane material of this invention is: (1) Constructing a gear-shaped PN-type heterojunction CuS-ZnIn2S4: CuS possesses excellent photothermal conversion performance and chemical stability, while ZnIn2S4 has a suitable visible light response range. The two are combined through a PN-type heterojunction to form a gear-like structure, achieving a highly efficient integration of photothermal conversion and photocatalytic functions. Under illumination, CuS can rapidly generate heat to reduce the adhesion of high-viscosity oils, while ZnIn2S4 simultaneously exerts its catalytic effect to degrade pollutants. The two functions, relying on the band-matching characteristics of the PN-type heterojunction, form a synergistic enhancement effect, effectively overcoming the limitations of single photocatalytic materials in treating complex pollutants.

[0010] Meanwhile, the unique hierarchical micro / nano morphology of gear-shaped CuS-ZnIn2S4 constructs a rough surface and a three-dimensional interconnected network. This special morphology can, on the one hand, provide more active sites by increasing the specific surface area, thereby enhancing the efficiency of photocatalytic reactions; on the other hand, it can form efficient mass transfer channels through the porous structure, significantly breaking through the flux limitations of traditional membrane materials and achieving rapid and efficient separation of emulsified oily wastewater. The charge separation advantage of the PN-type heterojunction and the structural advantage of the gear-shaped morphology form a dual synergy, jointly improving the overall performance of the material.

[0011] (2) Constructing a stable in-situ grown-supported nano-separation membrane A multi-step liquid-phase synthesis strategy was employed to firmly bond a gear-shaped CuS-ZnIn2S4 heterostructure to a nanofiber separation membrane substrate, forming a composite membrane system with unique morphology, dual-functional synergy, and high throughput. This technology overcomes the limitations of traditional supported membrane materials, which suffer from weak bonding and limited functionality. Through in-situ growth, the gear-shaped CuS-ZnIn2S4 is directly anchored onto the surface and pores of nanofibers. Its unique tooth-like protrusions construct a multi-level rough structure and three-dimensional interconnected channels. This significantly increases the specific surface area to provide sufficient photothermal conversion and photocatalytic active sites; furthermore, the inter-tooth gaps form an efficient mass transfer pathway, enabling the membrane to achieve a separation flux of 3900 L·m⁻¹ for oil-in-water emulsions. -2 ·h -1 above.

[0012] The gear-shaped heterostructure can achieve synergistic enhancement of photothermal response and photocatalysis. Under visible light, it can efficiently separate oil and water and simultaneously degrade organic pollutants such as antibiotics and dyes, forming an integrated treatment system of efficient separation and synergistic degradation. This breaks through the limitations of traditional single-function membrane materials that cannot simultaneously handle oil-water separation and organic pollutant treatment.

[0013] The present invention also provides a method for preparing the above-mentioned nano-separation membrane material for separating oily wastewater, comprising the following steps: S1 Preparation of nanofilms: Take the nano-based film, first perform pre-oxidation treatment, then immerse it in a mixed aqueous solution of copper sulfate pentahydrate and polyvinylpyrrolidone I, shake, then add thioacetamide aqueous solution, heat to 100-120℃, react, and obtain the nano-based film; S2 Preparation of nano-separation membrane materials: The nano-based membrane was immersed in a dopamine solution and shaken. Then, a composite modification solution containing zinc, indium, and sulfur was added, and the mixture was heated to 100-120°C to react. After solid-liquid separation, the membrane was washed and dried to obtain the nano-separation membrane material.

[0014] Preferably, in the mixed aqueous solution I of step S1, Cu 2+The concentration is 0.002-0.003 g / mL, and the concentration of polyvinylpyrrolidone is 0.003-0.008 g / mL.

[0015] Preferably, in step S1, the sulfur concentration of the thioacetamide aqueous solution is 0.002-0.003 g / mL.

[0016] Preferably, in step S1, the mixture is shaken for 20-50 minutes, then an aqueous solution of thioacetamide is added, and the mixture is heated to 100-120°C for 5-10 hours.

[0017] Preferably, in step S2, the composite modified liquid includes a solution A containing zinc and indium and a solution B containing sulfur. Solution A includes zinc nitrate and indium chloride, and solution B includes thioacetamide.

[0018] Preferably, solution A is a mixture of zinc nitrate hexahydrate, indium chloride tetrahydrate, and an organic solvent, and Zn 2+ The concentration is 0.002-0.008 mmol / mL, In 3+ The concentration is 0.002-0.02 mmol / mL.

[0019] Preferably, solution B is a mixture of thioacetamide and an organic solvent, and the sulfur concentration is 0.02-0.05 mmol / mL.

[0020] Preferably, in step S2, the mixture is shaken for 3-10 hours, then the composite modified liquid is added, and then heated to 100-120°C for 2-5 hours.

[0021] The nano-separation membrane material of the present invention can be used in the separation of emulsified oily wastewater, and has high separation flux and anti-fouling / synergistic enhanced treatment effect against complex pollutants.

[0022] The technical solution of the present invention has the following beneficial effects: Based on the problems of limited oil-water separation flux and poor anti-fouling performance of current separation membranes, this invention focuses on the synergistic effect of combining photothermal effect and photocatalytic effect, and designs and prepares a nano-separation membrane material with high separation flux and anti-fouling / synergistic enhanced treatment effect of complex pollutants.

[0023] A three-dimensional network structure of gear-shaped PN-type ZnIn2S4-CuS heterojunctions is constructed on the surface of the membrane material. The unique band structure of the PN-type heterojunction significantly improves carrier separation and transport efficiency, enhancing photocatalytic activity. Simultaneously, the synergistic effect of the heterojunction interface optimizes the light absorption range and photothermal conversion efficiency, achieving efficient conversion of light energy into heat and chemical energy. These two functions form a precise synergy within the heterojunction structure. The localized heating generated by the photothermal effect not only strengthens oil-phase separation and mass transfer processes but also promotes charge migration and reaction kinetics in the photocatalytic reaction. Meanwhile, the active species generated by photocatalysis can efficiently degrade pollutants activated by the photothermal effect, forming a synergistic effect of photothermal-enhanced catalysis and catalytic-promoted degradation. This effectively overcomes the limitations of traditional oil-water separation membrane materials that utilize single functions and non-synergistic systems, enabling efficient and deep treatment of complex oily wastewater.

[0024] Specifically, on the one hand, by constructing a three-dimensional network to form efficient mass transfer channels, the separation flux of the nano-separation membrane material for oil-in-water emulsions can reach 3921.44±196.1 L·m -2 ·h -1 Compared to existing membrane materials for oil-water and wastewater separation, this method significantly improves oil-water separation flux, providing a stable guarantee for high-throughput separation. On the other hand, the heterojunction effectively enhances charge transfer efficiency by improving photoresponse and reducing impedance, while dopamine, acting as a charge bridge, can transfer h from the CuS valence band. + With the ZnIn2S4 conduction band e - By temporarily storing charge carriers to delay recombination, this synergistic effect can significantly optimize the photothermal conversion performance of the material. Thanks to the above structural advantages, under simulated sunlight irradiation, the membrane surface temperature can rise to 61.67℃ or even higher within 15 seconds, which can effectively reduce the viscosity of the oil phase. Its permeation flux in simulated water-in-oil separation applications is significantly improved, further strengthening the core advantage of high separation flux.

[0025] In addition, the synergistic effect of gear-shaped CuS and ZnIn2S4 can effectively promote the efficient transfer of photogenerated electrons, generate abundant active substances, and rapidly degrade organic pollutants in oily wastewater, thus achieving the effect of photocatalytic degradation / self-cleaning.

[0026] In summary, the nano-separation membrane material of this invention achieves ultra-high oil-water separation flux through its gear-shaped ZnIn2S4-CuS heterojunction, and realizes photocatalytic-photothermal conversion performance by relying on the synergistic effect of ZnIn2S4-CuS and polydopamine layer, providing a feasible separation membrane material for the efficient separation and treatment of complex emulsified oily wastewater. Attached Figure Description

[0027] Figure 1The images show the microstructure and XRD diffraction patterns of different membrane materials in Experimental Example 1. (a) is the SEM image of the nano-based membrane, (b) is the SEM image of the CuS-PDA-ZnIn2S4@oPAN nano-separation membrane ZCP-2, (c) are the XRD diffraction patterns of the oPAN fiber-based membrane, CuS, ZnIn2S4 and CuS-PDA-ZnIn2S4@oPAN nano-separation membrane ZCP-2, and (d) are magnified XRD diffraction patterns of CuS and ZnIn2S4. Figure 2 The following are contact angle test diagrams of nano-separation membranes with different amounts of zinc nitrate hexahydrate in Experiment Example 2, where (a) is the water contact angle of different composite membranes, (b) is the underwater oil contact angle of ZCP-8, (c) is the emulsion separation performance of different composite membranes, and (d) is the emulsion separation performance of ZCP-8. Figure 3 The following are the stability test results of the ZCP-8 nano-separation membrane in Experiment Example 3 under different conditions: (a) is the result of treatment with 0.1M HCl, (b) is the result of treatment with 0.1M NaOH, (c) is the result of treatment with 1M NaCl, and (d) is the result of treatment with water at 80℃. Figure 4 The following are test results of the photocatalytic degradation performance of the nano-separation membranes with different amounts of zinc nitrate hexahydrate in Experiment Example 4. (a) shows the degradation performance of different composite membranes of TC, (b) shows the degradation performance of ZCP-8 of dyes, and (c) shows the cyclic degradation test of ZCP-8. Figure 5 The following is an analysis of the photothermal effect test results of the nano-separation membrane ZCP-8 in Experimental Example 5. In this figure, (a) and (b) show the surface temperature changes of the oPAN, CP and ZCP-8 composite membranes, (c) shows the UV-Vis diffuse reflectance spectra of CuS, ZnIn2S4 and CuS-ZnIn2S4, and (d) shows the photothermal response diagram of CuS. Figure 6 The graph shows the emulsion flux variation of the nano-separation membrane ZCP-8 in Experiment Example 6 under different conditions. In the graph, (a) is the transient photocurrent IT, (b) is the electrochemical impedance spectroscopy (EIS), (c) is the linear sweep voltammetry (LSV), and (d) is the emulsion flux variation of ZCP-8 under simulated sunlight conditions. Figure 7 The diagram shows the band structure and electron transfer of the ZCP-8 nano-separation membrane with different structures in Experimental Example 7. (a) is the MS curve of CuS, (b) is the MS curve of ZnIn2S4, (c) is the band gap of CuS and ZnIn2S4, and (d) is a schematic diagram of the band structure and electron transfer between CuS, PDA and ZnIn2S4. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, they are performed according to conventional conditions or conditions recommended by the manufacturer; where the manufacturers of the instruments, equipment, reagents, or raw materials used are not specified, they are all conventional products that can be purchased commercially.

[0029] This invention provides a nano-separation membrane material for separating oily wastewater. This nano-separation membrane material has high-performance effects such as high throughput and photothermal-photocatalytic synergistic antifouling, and can be applied to the separation of emulsified oily wastewater, etc.

[0030] The preparation method of the nano-separation membrane material for oily wastewater separation of the present invention includes the following steps: (1) Preparation of nanofilm (CP): A nanofilm (CP) with photothermal conversion properties was prepared using a hydrothermal method. The specific process is as follows: First, polyacrylonitrile (PAN) nanofiber base membranes are prepared by electrospinning. Then, the PAN nanofiber separation membranes are immersed in 0.2M potassium permanganate solution for pre-oxidation treatment to obtain oPAN fiber base membranes.

[0031] Take copper sulfate pentahydrate and polyvinylpyrrolidone (PVP), add them to deionized water to form mixture I, and control the Cu content. 2+ The concentration of the active ingredient is 0.002-0.003 g / mL, and the concentration of polyvinylpyrrolidone is 0.003-0.008 g / mL; thioacetamide is added to deionized water to form mixture II, and the sulfur concentration is controlled at 0.002-0.003 g / mL.

[0032] The oPAN fiber-based membrane is first immersed in mixture I and shaken for 20-50 minutes. Then, mixture I containing the oPAN fiber-based membrane is mixed with mixture II and added to a reaction vessel. The mixture is heated to 100-120℃ and reacted for 5-10 hours. After cooling, the membrane is removed to obtain a nano-based membrane (CP) with photothermal conversion properties.

[0033] (2) Preparation of nano-separation membrane materials: A photocatalytic-photothermal conversion CuS-PDA-ZnIn2S4@oPAN nano-separation membrane material was prepared using a solvothermal method. The specific process is as follows: Take the nano-based film prepared in step (1), immerse it in dopamine solution, and shake for 3-10 hours to construct a polydopamine (PDA) layer on the surface of the nano-based film.

[0034] Zinc nitrate hexahydrate and indium chloride tetrahydrate are mixed and dissolved in an organic solvent such as ethylene glycol to form solution A, while controlling the Zn content. 2+The concentration is 0.002-0.008 mmol / mL, In 3+ The concentration is 0.002-0.02 mmol / mL; separately, thioacetamide is dissolved in organic solvents such as ethylene glycol to form solution B, and the sulfur concentration is controlled to be 0.02-0.05 mmol / mL.

[0035] The nano-based membrane with the polydopamine layer was placed in a reaction vessel with solution A and solution B, heated to 100-120℃, and reacted for 2-5 hours. The membrane was then removed, washed, and dried to obtain the nano-separation membrane material, which can be denoted as CuS-PDA-ZnIn2S4@oPAN.

[0036] Example 1 Step 1: A nano-based membrane is prepared using a conventional electrospinning process. The PAN nano-separation membrane is then immersed in a 0.2M potassium permanganate solution for pre-oxidation treatment. After removal, it is washed and dried to obtain an oPAN fiber-based membrane.

[0037] Step 2: Take 0.375g of copper sulfate pentahydrate and 0.2g of PVP, and add them to 40mL of deionized water to form mixture I; take another 0.225g of thioacetamide, and add it to 40mL of deionized water to form mixture II.

[0038] Step 3: Immerse the oPAN fiber base membrane in solution I and shake for 30 minutes; then mix the mixture I containing the oPAN fiber base membrane with mixture II, add it to the reaction vessel, heat to 100°C, react for 6 hours, and after the reaction vessel cools down, remove it to obtain the nano-base membrane.

[0039] Step 4: Dissolve 0.2 mmol zinc nitrate hexahydrate and 0.4 mmol indium chloride tetrahydrate in 40 mL ethylene glycol to form solution A; separately dissolve 1.2 mmol thioacetamide in 40 mL ethylene glycol to form solution B.

[0040] Step 5: Place the nano-based membrane in a saturated dopamine solution and shake for 5 hours; then place it together with solution A and solution B in a reaction vessel and react at 100°C for 3 hours. After cooling, remove the membrane, wash and dry it to obtain the nano-separation membrane, denoted as ZCP-2.

[0041] Example 2 The difference between this embodiment and Example 1 is that in step four, the amount of zinc nitrate hexahydrate used is 0.4 mmol, and the prepared nano-separation membrane is designated as ZCP-4.

[0042] Example 3 The difference between this embodiment and Embodiment 1 is that in step four, the amount of zinc nitrate hexahydrate used is 0.6 mmol, and the prepared nano-separation membrane is designated as ZCP-6.

[0043] Example 4 The difference between this embodiment and Example 1 is that in step four, the amount of zinc nitrate hexahydrate used is 0.8 mmol, and the prepared nano-separation membrane is designated as ZCP-8.

[0044] Example 5 The difference between this embodiment and Example 1 is that in step four, the amount of zinc nitrate hexahydrate used is 1 mmol, and the prepared nano-separation membrane is designated as ZCP-10.

[0045] Experimental Example 1 This experimental example is based on the CuS@oPAN nano-separation membrane (step three) and the ZCP-2 nano-separation membrane (step five) from Example 1, characterizing their microstructure, and the results are as follows. Figure 1 As shown, (a) is the SEM image of the nano-based membrane, (b) is the SEM image of the CuS-PDA-ZnIn2S4@oPAN nano-separation membrane ZCP-2, (c) is the XRD diffraction analysis diagram of the oPAN fiber-based membrane, CuS, ZnIn2S4 and CuS-PDA-ZnIn2S4@oPAN nano-separation membrane ZCP-2, and (d) is the magnified XRD diffraction analysis diagram of CuS and ZnIn2S4.

[0046] Depend on Figure 1 It can be seen that the steric hindrance effect can effectively suppress excessive CuS aggregation, and small-sized CuS particles are uniformly anchored on the fiber surface, thereby forming an initial gear-shaped rough structure on the fiber, such as... Figure 1 (a) The addition of polydopamine enhances the adhesion between CuS and the fiber substrate, laying the foundation for the assembly of the second type of gear structure; subsequently, ZnIn2S4 is introduced via a solvothermal method, and ethylene glycol molecules adhere to the Zn on the surface of ZnIn2S4 via hydroxyl groups. 2+ and In 3+ Metal ions form stable coordination bonds, constructing a solvated shell to prevent particle aggregation and allow them to uniformly fill the fiber pores, such as... Figure 1 (b) forms a second type of gear; such as Figure 1 (c) XRD diffraction analysis confirmed that CuS and ZnIn2S4 were successfully loaded onto the oPAN film. The ZCP-2 composite film retained the characteristic peaks of the oPAN film at 16.9° and 29.2°, and added a new characteristic peak at 47.1° belonging to CuS and ZnIn2S4; Figure 1 (d) The peak positions of CuS and ZnIn2S4 are consistent with those of the standard card, which together prove that the heterogeneous nano-separation membrane ZCP-2 was successfully prepared.

[0047] Experimental Example 2 This experimental example uses nanomembranes with different amounts of zinc nitrate hexahydrate from Examples 1-5 as samples. Contact angle tests were conducted to characterize the wettability of the composite membranes. Furthermore, emulsion flux was characterized, and total organic carbon (TOC) testing was used to calculate the oil-water separation efficiency to demonstrate its effectiveness. The results are as follows: Figure 2 As shown, (a) is the water contact angle of different composite membranes, (b) is the underwater oil contact angle of ZCP-8, (c) is the emulsion separation performance of different composite membranes, and (d) is the emulsion separation performance of ZCP-8.

[0048] like Figure 2 (a) After the PAN film was oxidized to an oPAN film, the water contact angle decreased significantly from 147.6±1.4° to 38.7±1.8° due to the introduction of -COOH groups. The CuS-modified nanofilm showed a slight increase in water contact angle to 44.1±2.2° due to the relatively low surface energy of CuS, and the complete wetting time was extended to 7.8 s. Further construction of the ZCP composite film resulted in the -COOH groups reacting with the amino groups of polydopamine (PDA) to form -CONH2, and the introduction of hydroxyl groups by ZnIn2S4, leading to the lowest water contact angle for ZCP-8, at 16.5±2.4°. Figure 2 (b) The underwater oil contact angle (UOCA) test shows that ZCP-8 can achieve an underwater oil contact angle of 150° or higher. For various oil phases such as n-hexane, isooctane, petroleum ether, 1,3,5-trimethylbenzene, n-heptane and dichloroethane, its underwater oil contact angle remains at a high level, at 152.6±2.4°, 154.3±2.4°, 157.1±1.6°, 151.7±1.4°, 155.5±1.8° and 152.8±2.2° respectively, indicating that it has excellent underwater oil repellency performance.

[0049] This experimental example used 0.02 mg / mL sodium dodecyl sulfate (SDS) as the surfactant and a water-in-oil emulsion at a water-to-oil ratio of 100:1 to test the oil-water emulsion separation capability of the composite membrane. The separation capability of different types of water-in-oil emulsions was tested using ZCP-8. Adding two gear structures to the PAN fiber membrane can optimize the pore structure of the fiber membrane and enhance its separation performance. Figure 2 (c) When filtering SDS-stabilized water-in-hexane emulsions, PAN and oPAN exhibited high emulsion flux due to their unmodified pore structures, but both membranes had insufficient rejection rates, failing to achieve effective separation. For the CuS-modified PAN membrane, i.e., the CP membrane, although its flux decreased to 2853.5 ± 116.3 L·m⁻¹, the flux was significantly reduced. -2 ·h -1However, its rejection rate increased to 98.96±0.10%, indicating that the addition of CuS can regulate the pore structure of the nano-separation membrane and improve the membrane separation performance. After further modification, the obtained ZCP composite membrane exhibits a gear-like structure, which improves the separation performance by regulating the pore size and promoting mass transfer. Among them, the separation flux of ZCP-8 reached 3940.3±158.7 L·m -2 ·h -1 The rejection rate reached 99.14±0.08%, which is consistent with the results of the water contact angle experiment, confirming that the oil-water interface can be effectively controlled by adjusting the membrane surface composition and microstructure. Figure 2 (d) ZCP-8 exhibited excellent separation flux and oil rejection for various oil-in-water emulsions, specifically isooctane: 3747.8 ± 177.4 L·m -2 ·h -1 99.25±0.18%; n-Heptane: 3921.44±196.1 L·m -2 ·h -1 98.95±0.25%; 1,3,5-Trimethylbenzene: 3570.3±168.5 L·m -2 ·h -1 99.53±0.15%; Petroleum ether: 3774.1±173.7 L·m -2 ·h -1 , 99.10±0.13%.

[0050] Experimental Example 3 This experimental example uses the nano-separation membrane from Example 4 as a sample for stability testing. The separation performance was recorded during the process of exposure to strong acids, alkalis, salts, and high temperatures to demonstrate its high stability. Figure 3 The figures show the emulsion separation effect of ZCP-8 after soaking for 10 hours under different conditions. Specifically, (a) is the result of treatment with 0.1M HCl, (b) is the result of treatment with 0.1M NaOH, (c) is the result of treatment with 1M NaCl, and (d) is the result of treatment with water at 80℃.

[0051] To verify the practical applicability of ZCP-8, its flux stability under extreme environments was investigated, such as... Figure 3 In experiments (a) and (b) involving 10 hours of acid immersion (pH=1) and alkali immersion (pH=13), respectively, the flux decreased to 3466.5±173.3 and 3527.2±176.4 L·m⁻¹, respectively, due to slight corrosion of the gear structure on the film surface and local collapse of the pores caused by the strong acid and alkali environments. -2 ·h -1 However, the core separation efficiency was not significantly affected. And as... Figure 3(c) Under leaching conditions with 1M NaCl, the precipitation and accumulation of salt particles within the pores had a limited impact on the flux, remaining at 3668.6 ± 148.4 L·m⁻¹. -2 ·h -1 ;like Figure 3 (d) After treatment at 80℃ for 10 hours, the membrane flux remained stable at 3494.7±169.7 L·m⁻¹. -2 ·h -1 In summary, although the separation flux of ZCP-8 decreased slightly under repeated cycles and long-term exposure to extreme environments, it still remained at a high level. This is attributed to the physical support of the gear-shaped structure and the chemical synergy of CuS, ZnIn2S4, and PDA, which together ensured the integrity of the mass transfer channel, demonstrating its good application potential in relevant separation scenarios.

[0052] Test Example 4 This experimental example uses the nano-separation membranes from Examples 1-5 as samples to conduct photocatalytic degradation performance tests on tetracycline hydrochloride (TC) and dyes (MeB, CR), to verify that the coupling of photocatalytic technology and membrane separation technology can significantly improve the antifouling ability of the separation membrane and its ability to treat organic pollutants in oily wastewater. Figure 4 As shown, (a) shows the performance of different composite membranes in degrading TC, (b) shows the performance of ZCP-8 in degrading dyes, and (c) shows the cyclic degradation test of ZCP-8.

[0053] like Figure 4 (a) Under the action of persulfate (PMS), the ZCP series membranes showed a degradation rate of over 90% for 10 ppm tetracycline hydrochloride (TC) within 1 hour, with ZCP-8 achieving a degradation rate of 99.22%. This is attributed to the synergistic effect of gear-shaped CuS, PDA, and ZnIn2S4. The constructed high-roughness membrane surface provides more active sites and promotes efficient transfer of photogenerated electrons, continuously generating O. 2- Or reactive substances such as -OH groups, thereby rapidly degrading TC. In addition, such as... Figure 4 (b) ZCP-8 also exhibits excellent degradation effects on dye molecules at 20 ppm, eliminating 95% of the dye in just 0.5 hours and almost 100% within one hour. Furthermore... Figure 4 (c) In the cyclic degradation experiment of 20 ppm TC, the degradation rate exceeded 90% in 1 hour and remained above 91.5% in the 5th cycle, indicating that it has good cycle stability in continuous synergistic treatment of organic pollutants. In addition to excellent oil-water separation performance, the prepared composite membrane can also efficiently treat organic pollutants through the synergistic effect of photocatalysis and photothermal conversion under simulated sunlight irradiation.

[0054] Experimental Example 5 This experimental example uses the nano-separation membrane from Example 4 as a sample for photothermal testing to verify that the photothermal effect can increase the surface temperature of the composite membrane, thereby effectively reducing the viscosity of the oil. Furthermore, introducing photothermal treatment into the oil-water separation process can resolve irreversible membrane fouling accumulated during operation through in-situ self-cleaning. The experimental results are as follows: Figure 5 As shown, (a) and (b) are the surface temperature changes of oPAN, CP and ZCP-8 composite films, (c) are the UV-Vis diffuse reflectance spectra of CuS, ZnIn2S4 and CuS-ZnIn2S4, and (d) is a schematic diagram of the photothermal response of CuS.

[0055] like Figure 5 In (a) and (b), the surface temperature of the oPAN fiber-based membrane remained at 34.2°C for 15 seconds, the photothermal effect was negligible, and it provided almost no benefit to oil-water separation and photocatalysis. Figure 5 (c) CuS exhibits near-full-spectrum absorption characteristics in the 200-800 nm wavelength range, and its charge carriers oscillate in the alternating electromagnetic field of the incident light. For example... Figure 5 (d) When the incident light frequency matches the carrier oscillation frequency, localized surface plasmon resonance (LSPR) is triggered, efficiently converting electromagnetic energy into lattice vibrational thermal energy. Simultaneously, the PDA absorbs light energy and releases heat through molecular thermal motion. The synergistic effect of these two factors causes the surface temperature of the CP film to rise to 65.2℃ within 15 seconds. Similarly, for ZCP-8, the gear-shaped CuS-PDA-ZnIn2S4, through the synergistic effect of light absorption among its components, broadens the light response range and enhances the light energy capture capability. Under the same simulated sunlight irradiation, the film surface temperature can reach 61.67℃ within 15 seconds. This temperature exceeds the boiling point of most heavy oils, effectively reducing oil viscosity and providing favorable conditions for efficient separation.

[0056] Experimental Example 6 This experimental example uses the nano-separation membrane from Example 4 as a sample to conduct photocatalytic experiments. The aim is to verify that efficient carrier generation, separation, and charge transfer capabilities are core conditions for improving photocatalytic and photothermal conversion performance. Electrochemical techniques such as transient photocurrent (IT), electrochemical impedance spectroscopy (EIS), and linear sweep voltammetry (LSV) were used to investigate the efficient charge behavior of the ZCP membrane. The experimental results are as follows: Figure 6 As shown, (a) is the transient photocurrent IT, (b) is the electrochemical impedance spectroscopy (EIS), (c) is the linear sweep voltammetry (LSV), and (d) is the change in emulsion flux of ZCP-8 under simulated sunlight conditions.

[0057] like Figure 6(a) Under simulated sunlight irradiation by a 200W incandescent lamp, the heterojunction constructed from CuS and ZnIn2S4 exhibited good transient photocurrent performance. The photoresponse currents of CuS and ZnIn2S4 were 0.076 μA and 0.18 μA, respectively, increasing to 0.47 μA after assembly into a heterojunction. Furthermore, due to the extended lifetime of photogenerated electrons, the current did not significantly decay within the same time period and showed a clear enhancement trend, indicating a significant improvement in carrier separation efficiency. Figure 6 (b) Electrochemical impedance spectroscopy shows that the radius of curvature of the heterojunction is significantly smaller than that of the single material, confirming that the bandgap matching between CuS and ZnIn2S4 reduces interfacial impedance and promotes efficient charge transport. Figure 6 (c) In the linear sweep voltammetry method, the current density of CuS at an overpotential of 1.5 V is only 1.39 mA / cm². -2 ZnIn2S4 reaches 13.26 mA / cm -2 The composite heterojunction has a strength of 10.49 mA / cm². -2 This further confirms that heterojunctions can improve charge transfer efficiency by enhancing photoresponse and reducing impedance. For example... Figure 6 (d) Under simulated sunlight irradiation, the separation flux of ZCP-8 in separating soybean oil emulsions increased from 2242.0 ± 198.6 L·m⁻¹. -2 ·h -1 Increased to 4435.2±216.4 L·m -2 ·h -1 This indicates that the synergistic effect of photothermal response and photocatalysis can improve the efficiency of oil-water separation.

[0058] Experimental Example 7 This experimental example uses the nano-separation membrane from Example 4 as a sample. Electrochemical tests were conducted to investigate the band gap width and valence / conduction band positions between CuS, ZnIn2S4, and the heterojunction, to verify the influence and effect of the bonding mode and electron transfer direction between the heterojunctions. The results are as follows: Figure 7 As shown, (a) is the MS curve of CuS, (b) is the MS curve of ZnIn2S4, (c) is the band gap of CuS and ZnIn2S4, and (d) is a schematic diagram of the band relationship and electron transfer between CuS, PDA and ZnIn2S4.

[0059] like Figure 7(a) and (b), the Mott-Schottky curves show that the slope of the CuS curve is negative, while the slope of the ZnIn2S4 curve is positive, confirming that CuS is a P-type semiconductor and ZnIn2S4 is an N-type semiconductor. Combining the potential conversion relationship between Ag / AgCl and the standard hydrogen electrode SHE, i.e., EAg / AgCl relative to SHE = 0.197 eV, the fitted flat-band potentials (EfbSHE) are 1.047 eV and -0.633 eV, respectively. Figure 7 (c) Further measurements using UV-Vis diffuse reflectance spectroscopy revealed band gaps of 1.74 eV and 2.55 eV for CuS and ZnIn2S4, respectively. Based on this, the valence band (VB) and conduction band (CB) potentials of CuS were calculated to be 1.15 eV and -0.59 eV, respectively, while those of ZnIn2S4 were 1.82 eV and -0.73 eV, respectively. From this, the carrier transfer mechanism of the CuS-ZnIn2S4 heterojunction can be deduced, such as... Figure 7 (d) A large number of photogenerated holes h are generated in the valence band of P-type CuS. + Meanwhile, the conduction band of N-type ZnIn2S4 contains a rich accumulation of photogenerated electrons (e). - PDA, acting as a charge bridge, can transfer h from the valence band of CuS. + and e in the ZnIn2S4 conduction band - It delays recombination by temporarily storing charge carriers.

[0060] In summary, the experiments demonstrate that this invention, using bioadhesive polydopamine as a bridging agent, successfully prepared a multifunctional PAN-based nanofiber composite membrane (ZCP) for purifying high-viscosity emulsified oil contaminants by anchoring a gear-shaped CuS-ZnIn2S4 heterostructure onto an oxidized oPAN fiber substrate. This membrane integrates underwater superoleophobicity, photocatalytic self-cleaning ability, and photothermal conversion capability. On one hand, through modification with two types of gears, CuS and ZnIn2S4, the synergistic effect of the high surface energy and micro-nano roughness of the nano-separation membrane results in ultra-low oil adhesion, with an underwater oil contact angle reaching a maximum of 157.1±1.6°. On the other hand, the improved pore structure of the nano-separation membrane provides efficient mass transfer channels, enabling the membrane to achieve a permeation flux of up to 3921.44±196.1 L·m for surfactant-stabilized oil-in-water emulsions. -2 ·h -1The rejection rate exceeds 99.5%. It exhibits excellent antifouling performance even under harsh conditions of strong acids, alkalis, salts, and high temperatures. In the treatment of complex oil-in-water systems, the photothermal catalytic performance of the CuS-ZnIn2S4 heterostructure plays a crucial role. Under illumination, the composite membrane can degrade over 95% of tetracycline and various dyes within 60 minutes, and raise the membrane surface temperature to 61.67℃ within 15 seconds through photothermal conversion. This effectively reduces the adhesion of high-viscosity oil phases, nearly doubling the flux during photo-assisted separation. Furthermore, thanks to the PN-type heterojunction formed by P-type CuS and N-type ZnIn2S4, and the synergistic effect of polydopamine as an electron-hole transport station, the nano-separation membrane ZCP possesses highly efficient charge transport capabilities and considerable photoexcitation photocurrent. Therefore, the multifunctional nano-separation membrane material developed in this invention, combining photothermal conversion, photocatalytic degradation / self-cleaning, and anti-oil adhesion, has significant application advantages and prospects in the purification of complex emulsified oily wastewater.

[0061] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A nano-separation membrane material for separating oily wastewater, characterized in that, It includes a nano-based film and polydopamine@ZnIn2S4-CuS anchored on the surface of the nano-based film. The polydopamine@ZnIn2S4-CuS is a gear-shaped ZnIn2S4-CuS heterojunction material that bridges dopamine.

2. A method for preparing a nano-separation membrane material for separating oily wastewater as described in claim 1, characterized in that, Includes the following steps: S1 Preparation of nanofilms: Take the nano-based film, first perform pre-oxidation treatment, then immerse it in a mixed aqueous solution of copper sulfate pentahydrate and polyvinylpyrrolidone I, shake, then add thioacetamide aqueous solution, heat to 100-120℃, react, and obtain the nano-based film; S2 Preparation of nano-separation membrane materials: The nano-based membrane was immersed in a dopamine solution and shaken. Then, a composite modification solution containing zinc, indium, and sulfur was added, and the mixture was heated to 100-120°C to react. After solid-liquid separation, the membrane was washed and dried to obtain the nano-separation membrane material.

3. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 2, characterized in that, In the mixed aqueous solution I of step S1, Cu 2+ The concentration is 0.002-0.003 g / mL, and the concentration of polyvinylpyrrolidone is 0.003-0.008 g / mL.

4. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 2, characterized in that, In step S1, the sulfur concentration of the thioacetamide aqueous solution is 0.002-0.003 g / mL.

5. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 2, characterized in that, In step S1, shake for 20-50 minutes, add thioacetamide aqueous solution, and then heat to 100-120℃ for 5-10 hours.

6. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 2, characterized in that, In step S2, the composite modified liquid includes solution A containing zinc and indium and solution B containing sulfur. Solution A includes zinc nitrate and indium chloride, and solution B includes thioacetamide.

7. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 6, characterized in that, Solution A is composed of zinc nitrate hexahydrate, indium chloride tetrahydrate, and an organic solvent, and Zn 2+ The concentration is 0.002-0.008 mmol / mL, In 3+ The concentration is 0.002-0.02 mmol / mL.

8. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 6, characterized in that, Solution B is a mixture of thioacetamide and an organic solvent, with a sulfur concentration of 0.02-0.05 mmol / mL.

9. The method for preparing the nano-separation membrane material for separating oily wastewater according to claim 2, characterized in that, In step S2, shake for 3-10 hours, add the composite modified liquid, and then heat to 100-120℃ for 2-5 hours.

10. The application of the nano-separation membrane material for separating oily wastewater as described in claim 1, or the nano-separation membrane material prepared by any one of claims 2 to 9, in the separation of emulsified oily wastewater.

Citation Information

Patent Citations

  • Preparation method of PAN-based oil-water separation microporous membrane with photocatalysis function

    CN110860218A

  • Preparation method of photo-thermal driving PH response oil-water separation composite membrane

    CN117815707A

  • Visible light driven self-cleaning carbon nitride heterojunction oil-water separation membrane, preparation method and application

    CN115054948A

  • Method for preparing asymmetric integrated membrane material through controllable photo-thermal based on electrostatic spinning

    CN116212655A

  • Preparation method of oil-water separation super-hydrophobic paper loaded with CuS microspheres

    CN118558167A

Cited By

  • Aramid 1414-based aerogel membrane material for separating oily sewage as well as preparation method and application of aramid 1414-based aerogel membrane material

    CN122273343A